The influence of androgynous streamers on consumers’ product preferences - Wenting, Feng; Shuyun, Xue; Ying, Yang; Hai, Huang (Frontiers in Psychology, 2022)
Based on attachment theory, this study explores the impact of streamers' gender role (monosexual/ bisexual) on consumers’ preferences. The current research consists of two studies. Study 1 shows that the bisexual streamer elicits a higher product preference than the monosexual streamer in both male streamer and female streamer conditions. Study 2 includes two experiments. The findings discover that regardless of whether the streamer is male or female, when individuals have a high gender stereotype, the monosexual streamer leads to a higher product preference than the bisexual streamer. When individuals have a low gender stereotype, the bisexual streamer promotes a higher product preference than the monosexual streamer.